Analysis of inequality and energy-related CO2 emissions in Latin America and the Caribbean applying a Kaya factors decomposition methodology (2022)
This document is devoted to analyze the inequality in per capita CO2 emissions and energy-related CO2 emissions changes in Latin America and the Caribbean (LAC) during the period 1990-2018. To our best of knowledge, a simultaneous inequality decomposition by Kaya identity and Logarithmic Mean Divisia for index decomposition analysis (IDA-LMDI) of CO2 emissions changes has not been carried out before for LAC countries. In this paper we aim at filling this research gap based on the following question: What are the main macroeconomic drivers explaining inequality and changes in CO2 emissions trends in LAC during 1990 and 2018 and their policy implications? The study of inequality in per capita CO2 emissions and aggregate CO2 emissions time-series is relevant due the need to know the drivers that explain the changing trends in the past and to inform the debate around the establishment of mitigation agreements perceived as fair by all parties involved. In this paper, synthethic indicator of inequality called Theil index is applied to measure inequality in per capita emissions, along with a Kaya decomposition methodology to evalute the contribution of each driver to overall inequality. Similarly, an IDA-LMDI method is applied to analyze the changes of aggregate CO2 emissions during 1990 and 2018, decomposed into five factors: carbon intensity, share of fossil fuels, energy intensity, GDP per capita and population. Results show that the main factors contributing to inequality in per capita emissions in LAC are the energy and carbon intensity. Likewise, it is observed that the results are strongly influenced by the performance of Brazil. As for the changes in CO2 emissions trends, it is also observed that energy intensity is one of the main drivers but the most important are GDP per capita and population. Policy implications presented discuss the importance of improvements in energy efficiencies and changes in production structures of LAC countries as well as the decarbonization of the energy mix to achieve mitigation targets.